1,Tìm x:
3(x+3)=2(x-5) x4-27x=0
(3x+1)3=27
2,Tìm x và y
xy+9+2x=6 (x;y thuộc z)
Tìm x , biết :
a. \(\left(x-2\right)^3-\left(x-3\right)\left(x^2+3x+9\right)+6\left(x+1\right)^2=15\)
b. \(2x^3-50x=0\)
c.\(5x^2-4\left(x^2-2x+1\right)-5=0\)
d. \(x^3-x=0\)
e. \(27x^3-27x^2+9x-1=1\)
a) Ta có: \(\left(x-2\right)^3-\left(x-3\right)\left(x^2+3x+9\right)+6\left(x+1\right)^2=15\)
\(\Leftrightarrow x^3-6x^2+12x-8-x^3+27+6\left(x^2+2x+1\right)=15\)
\(\Leftrightarrow-6x^2+12x+19+6x^2+12x+6=15\)
\(\Leftrightarrow24x+25=15\)
\(\Leftrightarrow24x=-10\)
hay \(x=-\dfrac{5}{12}\)
b) Ta có: \(2x^3-50x=0\)
\(\Leftrightarrow2x\left(x-5\right)\left(x+5\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=5\\x=-5\end{matrix}\right.\)
c) Ta có: \(5x^2-4\left(x^2-2x+1\right)-5=0\)
\(\Leftrightarrow5x^2-4x^2+8x-4-5=0\)
\(\Leftrightarrow x^2+8x-9=0\)
\(\Leftrightarrow\left(x+9\right)\left(x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-9\\x=1\end{matrix}\right.\)
d) Ta có: \(x^3-x=0\)
\(\Leftrightarrow x\left(x-1\right)\left(x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=1\\x=-1\end{matrix}\right.\)
e) Ta có: \(27x^3-27x^2+9x-1=1\)
\(\Leftrightarrow\left(3x\right)^3-3\cdot\left(3x\right)^2\cdot1+3\cdot3x\cdot1^2-1^3=1\)
\(\Leftrightarrow\left(3x-1\right)^3=1\)
\(\Leftrightarrow3x-1=1\)
\(\Leftrightarrow3x=2\)
hay \(x=\dfrac{2}{3}\)
Tìm x
a, (x+2)^3 - x(x^2+6x-3)=0
b,(x+4)^3 - x(x+6)^2=7
c, (x-1)^3 - x(x^2-3x-2)=0
d,1000x^3+90x(10x+3)+27=0
e,125x^3+15x(5x+1)= -1
f, 27x^3+45x(3x+5)+133=0
a, \(\left(x+2\right)^3-x\left(x^2+6x-3\right)=0\Leftrightarrow x^3+4x^2+4x+2x^2+8x+8-x^3-6x^2+3x=0\)
\(\Leftrightarrow15x+8=0\Leftrightarrow x=-\frac{8}{15}\)
b, \(\left(x+4\right)^3-x\left(x+6\right)^2=7\Leftrightarrow12x+64=0\Leftrightarrow x=-\frac{19}{4}\)làm tắt:P
Tự làm nốt nhé
a) x2(x - 5) + 5 - x = 0; b) 3x4 - 9x3 = -9x2 + 27x;
c) x2(x + 8) + x2 = -8x; d) (x + 3)(x2 -3x + 5) = x2 + 3x.
e) 3x(x - 1) + x - 1 = 0;
f) (x - 2)(x2 + 2x + 7) + 2(x2 - 4) - 5(x - 2) = 0;
g) (2x - 1)2 - 25 = 0;
h) x3 + 27 + (x + 3)(x - 9) = 0.
i)8x3 - 50x = 0; k) 2(x + 3)-x2 - 3x = 0;
m)6x2 - 15x - (2x - 5)(2x + 5) =
a: \(\Leftrightarrow\left(x-5\right)\left(x+1\right)\left(x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=5\\x=-1\\x=1\end{matrix}\right.\)
d: \(\Leftrightarrow\left(x+3\right)\left(x^2-4x+5\right)=0\)
\(\Leftrightarrow x+3=0\)
hay x=-3
Tìm x, biết:
a) x 2 (x - 5) + 5 - x = 0; b) 3 x 4 - 9 x 3 = -9 x 2 + 27x;
c) x 2 (x + 8) + x 2 = -8x; d) (x + 3)( x 2 -3x + 5) = x 2 + 3x.
Tìm x:
a)x(2x-4)-(x-2)(2x+3)
b)x(3x+2)+(x+1)^2-(2x-5)(2x+5)=-12
c)(x-1)(x^2+x+1)-x(x-3)^2=6x^2
d)x^2-x=0
e)(x+2)(x-3)-x-2=0
f)3x^3-27x
x(2x-4)-(x-2)(2x+3)
<=> (2x2 - 4x ) - (2x2 - 3x - 4x -6=0
<=> 2x2 - 4x -2x2 -3x - 4x + 6 =0
<=> -3x + 6 =0
<=> -3x = 6
<=> x = -(6/3) = -2
Chứ bằng mấy, mk thấy ko có bằng nên làm mặc định là 0
Bài 1 : Tìm x
a. ( 2x + 1 )^2 - 4( x + 2 )^2 = 9
b.( 3x - 1 )^2 + 2( x + 3 )^2 + 11( x + 1 ).(1 - x ) = 6
c. 8x^3 - 12x^2 + 6x - 1 = 0
d. x^3 + 9x^2 + 27x + 27 = 0
Bài 1: Tìm x
a) Ta có: \(\left(2x+1\right)^2-4\left(x+2\right)^2=9\)
\(\Leftrightarrow4x^2+4x+1-4\left(x^2+4x+4\right)-9=0\)
\(\Leftrightarrow4x^2+4x+1-4x^2-16x-16-9=0\)
\(\Leftrightarrow-12x-24=0\)
\(\Leftrightarrow-12x=24\)
hay x=-2
Vậy: x=-2
b) Ta có: \(\left(3x-1\right)^2+2\left(x+3\right)^2+11\left(x+1\right)\left(1-x\right)=6\)
\(\Leftrightarrow9x^2-6x+1+2\left(x^2+6x+9\right)-11\left(x-1\right)\left(x+1\right)-6=0\)
\(\Leftrightarrow9x^2-6x+1+2x^2+12x+18-11\left(x^2-1\right)-6=0\)
\(\Leftrightarrow11x^2+6x+12-11x^2+11=0\)
\(\Leftrightarrow6x+23=0\)
\(\Leftrightarrow6x=-23\)
hay \(x=-\frac{23}{6}\)
Vậy: \(x=-\frac{23}{6}\)
c) Ta có: \(8x^3-12x^2+6x-1=0\)
\(\Leftrightarrow\left(2x\right)^3-3\cdot\left(2x\right)^2\cdot1+3\cdot2x\cdot1^2-1^3=0\)
\(\Leftrightarrow\left(2x-1\right)^3=0\)
\(\Leftrightarrow2x-1=0\)
\(\Leftrightarrow2x=1\)
hay \(x=\frac{1}{2}\)
Vậy: \(x=\frac{1}{2}\)
d) Ta có: \(x^3+9x^2+27x+27=0\)
\(\Leftrightarrow x^3+3\cdot x^2\cdot3+3\cdot x\cdot3^2+3^3=0\)
\(\Leftrightarrow\left(x+3\right)^3=0\)
\(\Leftrightarrow x+3=0\)
hay x=-3
Vậy: x=-3
a) (2x + 1)2 - 4(x + 2)2 = 9
4x2 + 4x + 1 - 4(x2 + 4x + 4) = 9
4x2 + 4x + 1 - 4x2 - 16x - 16 = 9
-12x - 15 = 9
-12x = 9 + 15
-12x = 24
x = 12 : (-2)
x = -2
b) (3x - 1)2 + 2(x + 3)2 + 11(x + 1)(1 - x) = 6
9x2 - 6x + 1 + 2(x2 + 6x + 9) - 11(x + 1)(x - 1) = 6
9x2 - 6x + 1 + 2x2 + 12x + 18 - 11(x2 - 1) = 6
9x2 - 6x + 1 + 2x2 + 12x + 18 - 11x2 + 11 = 6
6x + 30 = 6
6x = 6 - 30
6x = -24
x = -24 : 6
x = -4
c) 8x3 - 12x2 + 6x - 1 = 0
(2x)3 - 3.(2x)2.1 + 3.2x.12 - 13 = 0
(2x - 1)3 = 0
2x - 1 = 0
2x = 1
x = 1/2
d) x3 + 9x2 + 27x + 27 = 0
x3 + 3.x2.3 + 3.x.32 + 33 = 0
(x + 3)3 = 0
x + 3 = 0
x = 0 - 3
x = -3
tìm x
a) (x+2)(x+3)-(x-2)(x+5)=6
b) (3x+2)(2x+9)-(x+2)(6x+1)=(x+1)-(x-6)
c) 3(2x-1)(3x-1)-(2x-3)(9x-1)=0
a: Ta có: \(\left(x+2\right)\left(x+3\right)-\left(x-2\right)\left(x+5\right)=6\)
\(\Leftrightarrow x^2+5x+6-x^2-3x+10=6\)
\(\Leftrightarrow2x=-10\)
hay x=-5
b: Ta có: \(\left(3x+2\right)\left(2x+9\right)-\left(x+2\right)\left(6x+1\right)=\left(x+1\right)-\left(x-6\right)\)
\(\Leftrightarrow6x^2+27x+4x+18-6x^2-x-12x-2=x+1-x+6\)
\(\Leftrightarrow18x+16=7\)
hay \(x=-\dfrac{1}{2}\)
c: Ta có: \(3\left(2x-1\right)\left(3x-1\right)-\left(2x-3\right)\left(9x-1\right)=0\)
\(\Leftrightarrow3\left(6x^2-2x-3x+1\right)-\left(18x^2-2x-27x+3\right)=0\)
\(\Leftrightarrow18x^2-15x+3-18x^2+27x-3=0\)
hay x=0
Tìm x
a.(x+2).(x+3)-(x-2).(x+5) = 0
b. (2x+3).(x-4)+(x-5)(x+2) = (3x-5)(x-4)
c. (3x+2)(2x+9)-(x+2)(6x+1) = x+1-(x-6)
d. 3( 2x-1).(3x-1)-(2x-3).(9x-1)=0
(x+2)(x+3)-(x-2)(x+5)=0
=> x2+5x+6-x2-3x+10=0
=>2x+16=0
=>2x=-16
=>x=-8
Tìm x biết:
a,(2x+3/5)^2-9/25=0
b,(3x-1).(-1/2x+5)=0
c, (7/5)^x+1-(1/5)^x=-4/625
d,(2/3)^x+2+(2/3)^x+1=20/27
a) \(\left(2x+\frac{3}{5}\right)^2-\frac{9}{25}=0\)
\(\left(2x+\frac{3}{5}\right)^2=\frac{9}{25}\)
\(\left(2x+\frac{3}{5}\right)^2=\left(\frac{3}{5}\right)^2\)
\(=>2x+\frac{3}{5}=\frac{3}{5}\)
\(2x=\frac{3}{5}-\frac{3}{5}\)
\(2x=0\)
\(x=0:2\)
\(x=0\)
b) \(\left(3x-1\right).\left(-\frac{1}{2x}+5\right)=0\)
=> \(\left(3x-1\right)=0\)hoặc \(\left(-\frac{1}{2x}+5\right)=0\)hoặc \(\left(3x-1\right)\)và\(\left(-\frac{1}{2x}+5\right)\)cùng bằng 0.
\(\orbr{\begin{cases}3x-1=0\\-\frac{1}{2x}+5=0\end{cases}}=>\orbr{\begin{cases}3x=1\\-\frac{1}{2x}=-5\end{cases}}=>\orbr{\begin{cases}x\in\varnothing\\2x=\frac{1}{5}\end{cases}}=>x=\frac{1}{5}:2=>x=\frac{1}{10}\)
a) \(\left(2x+\frac{3}{5}\right)^2-\frac{9}{25}=0\)
\(\left(2x+\frac{3}{5}\right)^2=0+\frac{9}{25}\)
\(\left(2x+\frac{3}{5}\right)^2=\frac{9}{25}\)
\(\left(2x+\frac{3}{5}\right)^2=\left(\frac{3}{5}\right)^2\)
\(\orbr{\begin{cases}2x+\frac{3}{5}=\frac{3}{5}\\2x+\frac{3}{5}=-\frac{3}{5}\end{cases}}\)
\(\orbr{\begin{cases}x=0\\x=-\frac{3}{5}\end{cases}}\)
b) \(\left(3x-1\right)\left(-\frac{1}{2}x+5\right)=0\)
\(\left(3x-1\right)\left(-\frac{x}{2}+5\right)=0\)
\(\left(3x-1\right)\left(5-\frac{x}{2}\right)=0\)
\(\orbr{\begin{cases}3x-1=0\\5-\frac{x}{2}=0\end{cases}}\)
\(\orbr{\begin{cases}x=\frac{1}{3}\\x=10\end{cases}}\)